Bacteria-based artificial diets modulate larval development, survival and gut microbiota of two insect pests - A.O. Adesemoye; S. Antony-Babu; E.M. Nagy; B.D. Kafle; T.A. Gregory; C. Xiong; H.Y. Fadamiro (Biological Control)
Crop damage caused by insect pests results in substantial economic losses. The most widely used control methods, chemical pesticides, are losing efficacy and have deleterious environmental and health impacts. The goal of this study was to evaluate plant growth-promoting rhizobacteria (PGPR) strains blended as consortia for the management of insect pests through the impact on insect-gut microbiota. PGPR isolates were recovered from corn rhizosphere in Texas and characterized through 16S rRNA gene sequencing. Eight strains belonging to diverse taxa selected through prescreening were combined in three different blends (consortia), added into an insect artificial diet, and fed to larvae of corn earworm (Helicoverpa zea [Boddie, 1850]) and tobacco budworm (Chloridae virescens [Fabricius, 1777]). Insect growth and development was monitored, and gut microbiota was assessed through direct isolation and 16S rRNA sequencing approaches. The inoculated diet resulted in significant reduction in larval weight for both insect species compared to the control and caused changes in the taxonomic diversity and evenness of H. zea gut microbiota. The results of the isolation and 16S rRNA sequencing were generally in agreement and showed a higher population and dominance of bacilli but less diversity of other taxa in PGPR blend treatments compared to control. While the mechanism of the changes in gut microbiota is currently unknown, understanding how to utilize bacterial strains to manipulate insect’s gut microbiota and health is important for developing sustainable pest management strategies. Future studies should elucidate the mechanisms and how to effectively deploy these findings for field applications.